Brain BDNF levels are dependent on cerebrovascular endothelium‐derived nitric oxide. (14th July 2016) - Banoujaafar, Hayat; Monnier, Alice; Pernet, Nicolas; Quirié, Aurore; Garnier, Philippe; Prigent‐Tessier, Anne; Marie, Christine
Abstract: Scientific evidence continues to demonstrate a link between endothelial function and cognition. Besides, several studies have identified a complex interplay between nitric oxide (NO) and brain‐derived neurotrophic factor (BDNF), a neurotrophin largely involved in cognition. Therefore, this study investigated the link between cerebral endothelium‐derived NO and BDNF signaling. For this purpose, levels of BDNF and the phosphorylated form of endothelial NO synthase at serine 1177 (p‐eNOS) were simultaneously measured in the cortex and hippocampus of rats subjected to either bilateral common carotid occlusion ( n = 6), physical exercise ( n = 6) or a combination of both ( n = 6) as experimental approaches to modulate flow‐induced NO production by the cerebrovasculature. Tropomyosin‐related kinase type B (TrkB) receptors and its phosphorylated form at tyrosine 816 (p‐TrkB) were also measured. Moreover, we investigated BDNF synthesis in brain slices exposed to the NO donor glyceryl trinitrate. Our results showed increased p‐eNOS and BDNF levels after exercise and decreased levels after vascular occlusion as compared to corresponding controls, with a positive correlation between changes in p‐eNOS and BDNF ( r = 0.679). Exercise after vascular occlusion did not change levels of these proteins. Gyceryl trinitrate increased proBDNF and BDNF levels in brain slices, thus suggesting a possible causal relationship between NO and BDNF. Moreover, vascular occlusion, like exercise, resulted in increased TrkB and p‐TrkB levels, whereas no change was observed with the combination of both. These results suggest that brain BDNF signaling may be dependent on cerebral endothelium‐derived NO production. Abstract : The changes in cerebrovascular endothelial nitric oxide synthase (eNOS) activity induced by physical exercise and bilateral common carotid occlusion translated into parallel changes in brain‐derived neurotrophic factor (BDNF) levels in both the cortex and hippocampus. When induced after vascular occlusion, physical exercise failed to increase eNOS activity and BDNF levels, whereas the exposure of brain slices to a NO donor induces elevation in BDNF and proBDNF levels.